Nutritive Evaluation Of Prawn Waste As Cattle Feed - George Varughese (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1997)
Prawn waste collected from three major fish landing areas viz., Kochi, Kodungalloor and Kozhikode contained on an average 21.9 per cent dry matter, 37.6 per cent crude protein, 24.4 per cent total ash, 17.4 per cent acid detergent fibre, 8.91 per cent calcium and 1.72 per cent phosphorus. Prawn waste procured from Kochi area had higher dry matter, total ash, acid detergent fibre, calcium and phosphorus and less of crude protein. The results of in situ degradability studies carried out in three rumen fistulated cows indicated that the dry matter and crude protein degradabilities of prawn waste ranged from 35 to 45 and 44 to 56 per cent respectively. Prawn waste from Kochi area had lower (P<0.0l) dry matter and crude protein degradabilities than the other two areas. Metabolism trials conducted in adult, non-producing cattle using standard concentrate mixtures containing 0, 10 or 20 per cent prawn waste registered in the ration digestibility coefficients to the extent of 53 to 56, 52 to 55, 63 to 67, 61 to 64 and 60 to 63 per cent for dry matter, crude protein, ether extract, crude fibre and nitrogen free extract respectively. There was no significant difference (P<0.05) in the digestibilities of nutrients in the three treatments. The animals on all the rations were on positive nitrogen balance. It is inferred that prawn waste can be safely and economically incorporated upto 20 per cent level in the concentrate mixtures of adult non-producing cattle.